2022
DOI: 10.22146/jpti.71761
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Demography of Helopeltis bradyi Waterhouse (Hemiptera: Miridae) Reared on Cucumbers

Abstract: Helopeltis bradyi is often used as for research and is required in large numbers. The insects were obtained from cacao plants and reared with cucumber fruit in the laboratory. This study aimed to determine the biology and demography of H. bradyi reared on cucumber under laboratory conditions. The demographic parameters observed were net reproduction rate (Ro), gross reproduction rate (GRR), intrinsic growth rate (r), average generation period (T), and population doubling (DT). The results showed that the egg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Pests that attack the cultivation of fungi respondents 1 and 2 were mites (Tyrophagus putrescentiae). Mites attack at all stages of black ear mushroom, ranging from pure cultures, seedlings, samples, to growing medium [25]. Therefore, mites are infectious.…”
Section: Pest Controlmentioning
confidence: 99%
“…Pests that attack the cultivation of fungi respondents 1 and 2 were mites (Tyrophagus putrescentiae). Mites attack at all stages of black ear mushroom, ranging from pure cultures, seedlings, samples, to growing medium [25]. Therefore, mites are infectious.…”
Section: Pest Controlmentioning
confidence: 99%
“…The highest number of eggs was produced from a pair of H. bradyi originating from cacao plants in Sleman District, followed by Kulon Progo District and Batang District, respectively 88 (Table 1), 28 (Table 2), and 14 eggs/ generation (Table 3). Research conducted by Simanjuntak et al (2022) on H. bradyi from Kulon Progo which was also reared using cucumber at 28−30°C showed that three pairs of imago were able to produce 304 eggs.…”
Section: Cohort and Life Table Of Helopeltis Bradyimentioning
confidence: 99%
“…The changes that occur continuously encouraged H. bradyi to adapt and be able to maintain the population size. Simanjuntak et al (2022), stated that young Helopeltis were not able to adapt to changes in feeding sources and disturbances when the rearing area was cleaned. This is supported by Sétamou et al (1999), which stated that the survival of the insect H. bradyi was strongly influenced by the type of host plant, even though it is classified as a polyphagous insect.…”
Section: Cohort and Life Table Of Helopeltis Bradyimentioning
confidence: 99%
See 1 more Smart Citation